Tiền kỹ thuật số của ngân hàng trung ương (CBDC) tại các nước đang phát triển: Khảo lược và hướng nghiên cứu mới - Vương Thị Hương, Giang; Nguyễn Hữu, Mạnh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The central bank plays an important role in promoting macroeconomic stability and economic growth through effective monetary policies. A newly emerging field that has attracted attention in recent years is the Central Bank Digital Currency (CBDC). CBDC is a digital version of cash issued and managed by central banks, providing higher security and stability than private digital assets. The application of CBDC may bring both benefits and risks to the economy, which has been a concern in recent times. This research will focus on analyzing the impacts of CBDC on the economies of developing countries, particularly in the implementation of monetary policies, financial system stability, and technical aspects when applied. The author also aim to identify potential future research directions in the context of developing countries, including Vietnam.